Experimental Simulation of Methane Hydrate Extraction at High Pressure Conditions: Influence of the Sediment Bed - Agudo, J. R.; Park, J.; Luzi, G.; Williams, M.; Rauh, C.; Wierschem, A.; Delgado, A. (Journal of Physics: Conference Series, 2017)
Being a clean alternative to other fossil fuels, Methane Hydrate (MH) is currently considered as one of the most important potential sources for hydrocarbon fuels [1]. In addition, the high energy density of MH and its stability at higher temperatures as compared to LNG (Liquefied Natural Gas) makes MH a potential greener method for energy transportation. At the same time, the low thermodynamic stability of MH strongly questions the future exploitation of gas hydrate deposits, turning its extraction into a possible geohazard [2]. Fluctuations in pressure, temperature, salinity, degree of saturation or sediment bed properties may cause methane gas release from the water lattice. We experimentally study the influence of the sediment bed geometry during formation-dissociation of MH. For this purpose, MH is synthesized within regular substrates in a 93 cm3 high pressure vessel. The regular substrates are triangular and quadratic arrangements of identical glass spheres with a diameter of 2 and 5 mm, respectively. MH formation within regular substrate reduces the possibility of spontaneous nucleation to a unique geometrical configuration. This fact permits us to characterize the kinetics of MH formation-dissociation as a function of the sediment bed geometry. Preliminary experimental results reveal a strong dependence of MH formation on the geometry of the regular substrate. For instance, under the same pressure and temperature, the kinetics of MH production is found to change by a factor 3 solely depending on the substrate symmetry, i.e. triangular or quadratic.